2015
DOI: 10.1142/s2010007815500037
|View full text |Cite
|
Sign up to set email alerts
|

An Economy-Wide Analysis of Climate Change Impacts on Agriculture and Food Security in Bangladesh

Abstract: Bangladesh is one of the most vulnerable countries to climate change (CC) with higher temperatures reducing crop yields and sea level rise decreasing arable land supply. The Government of Bangladesh aspires to offer its people a comparable standard of living to that of middle-income countries by 2021. Bangladesh's population will reach 247 million by 2050 and GDP is projected to grow annually by 7.9%. With increasing population density, greater demand for resources, and CC impacts, adaptation and mitigation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In the past, only a few studies have used the CGE model to investigate the impact of climate change on Bangladesh. As a result, the findings of this study support prior research (Yu et al 2010;Banerjee et al 2014Banerjee et al , 2015 that found climate change negatively impacts the total economy. The results of this study also show that the overall economy in Bangladesh grew negatively due to climate change issues, which poses a significant concern for Bangladesh's economic development and food security.…”
Section: Model Simulation Results and Analysissupporting
confidence: 89%
“…In the past, only a few studies have used the CGE model to investigate the impact of climate change on Bangladesh. As a result, the findings of this study support prior research (Yu et al 2010;Banerjee et al 2014Banerjee et al , 2015 that found climate change negatively impacts the total economy. The results of this study also show that the overall economy in Bangladesh grew negatively due to climate change issues, which poses a significant concern for Bangladesh's economic development and food security.…”
Section: Model Simulation Results and Analysissupporting
confidence: 89%
“…For instance, global climate change is estimated to reduce Bangladesh’s GDP by 29,925 million Takas (−0.11 per cent) by 2030, with agricultural output falling by −1.23 per cent accompanied with a 1.52 per cent increase in food imports. The forecast for other South Asian countries is no better than that for Bangladesh (Banerjee et al , 2015). South Asia, though not a significant contributor of greenhouse gases (GHGs), bears a disproportionate brunt of the climate change impacts ranging from floods caused by glacier lake outburst floods (GLOFs), rising sea level, salinity, water scarcity and extreme weather events.…”
Section: Introductionmentioning
confidence: 95%
“…In Bangladesh, one study has found that the overall effect of climate change by 2030 on national income is likely be small. But the effect on the agricultural sector is projected to be much larger, leading to reduced output, increased imports, and reduced caloric consumption (Banerjee et al 2015).…”
Section: Climate Change Food Security and Nutritionmentioning
confidence: 99%